18F-Fluorodeoxyglucose positron emission tomography and infectious diseases: current applications and future perspectives. Issue 2 (April 2017) - Bassetti, Matteo; Carnelutti, Alessia; Muser, Daniele; Righi, Elda; Petrosillo, Nicola; Di Gregorio, Fernando; Werner, Thomas J.; Alavi, Abass
Abstract : Purpose of review: 18F-Fluorodeoxyglucose positron emission tomography/computed tomography is a well-established technique for diagnosis and management of a number of neoplastic conditions. However, in recent years the body of literature regarding its potential role in infectious diseases has progressively increased, with promising results. Recent findings: So far 18F-fluorodeoxyglucose positron emission tomography/computed tomography has a well-established role and is recommended by guidelines only in a few settings, such as prosthetic valve endocarditis, vascular device infections, and chronic osteomyelitis. However, even the lack of large, prospective randomized trials, an increasing number of small series and case reports suggest a potential role in the diagnosis, disease staging, and monitoring of treatment response of several other infective conditions. Summary: In this article, we summarize the available evidence and potential future applications of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in the diagnosis and management of infectious diseases.